2010
DOI: 10.1007/s10029-010-0649-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of primary versus incisional ventral hernias: time to recognize the differences?

Abstract: The LOP and LOS are longer after the laparoscopic repair of incisional than for primary ventral hernias. This disparity should be kept in mind when counseling patients and while designing trials investigating laparoscopic ventral hernia repairs (LVHRs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
3
15
0
1
Order By: Relevance
“…Another analysis of the literature on elective surgery of ventral and incisional hernias identified inconsistencies in reporting of peri- and postoperative variables and poor definition of variables ( 29 ). A further problem is the pooling of primary ventral hernias and incisional hernias in many studies, meta-analyses and systematic reviews ( 30 33 ). Several studies have demonstrated that there is a significant difference between the outcomes for primary abdominal wall hernias and incisional hernias, hence these hernia entities should not be pooled ( 30 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another analysis of the literature on elective surgery of ventral and incisional hernias identified inconsistencies in reporting of peri- and postoperative variables and poor definition of variables ( 29 ). A further problem is the pooling of primary ventral hernias and incisional hernias in many studies, meta-analyses and systematic reviews ( 30 33 ). Several studies have demonstrated that there is a significant difference between the outcomes for primary abdominal wall hernias and incisional hernias, hence these hernia entities should not be pooled ( 30 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…A further problem is the pooling of primary ventral hernias and incisional hernias in many studies, meta-analyses and systematic reviews ( 30 33 ). Several studies have demonstrated that there is a significant difference between the outcomes for primary abdominal wall hernias and incisional hernias, hence these hernia entities should not be pooled ( 30 33 ). Against that background the present review aims to identify which data are available on the sublay/retro-rectus operation to demonstrate that this is the best open technique for repair of only incisional hernia.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective population-based studies reported conflicting results [12][13][14][15][16][17][18]. Excellent results, when dealing with primary ventral hernias, have been published [19][20][21]. Laparoscopic approach could play a role in reducing perioperative morbidity and cardio-circulatory overload in elderly patients.…”
Section: Luis Sanchez Lapo Bencinimentioning
confidence: 96%
“…The findings of three further systematic reviews and meta-analyses must be analyzed in a critical light with respect to the key question addressed here since they included studies with primary abdominal wall hernias and incisional hernias, i.e., mixed patient collectives, as well as the laparoscopic technique ( 38 40 ). Numerous studies have demonstrated that the outcomes for repair of primary abdominal wall hernias and incisional hernias differ highly significantly and therefore should not be combined ( 41 45 ). Moreover, the mesh position as underlay was not defined exactly.…”
Section: Resultsmentioning
confidence: 99%